Manajemen Fisioterapi pada Post Rekonstruksi PCL Fase 1: Case Report - Syafira, Khansa; Fatmarizka, Tiara; Mardianto, Halim (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Football is a sport that is prone to injuries, one of which is a torn posterior cruciate ligament (PCL). The PCL is a ligament that acts as the main barrier to posterior translation of the knee. The treatment of PCL injuries is divided into 2, namely conservative (surgery) and non-conservative, depending on the severity. In conservative treatment, it is necessary to perform early mobilization after the injury to increase ROM and stability. Case Presentation: a 15-year-old patient post PCL reconstruction with complaints of, swelling in the left knee, limited Range Of Motion (ROM) and decreased of muscle strength came to RSUD KRMT Wongsonegoro Semarang to carry out rehabilitation. Management and Outcome: Rehabilitation had been done three times a week to facilitate the improvement of knee ROM and muscle strength and decreased the swelling. Rehabilitation consists of quadset, SLR, Side SLR, ankle pumping, wall slide, prone hang, and gait training. Discussion: Rehabilitation immediately following conservative treatment helps to improve muscle strength and ROM and reduce knee swelling. In addition, strengthening exercises on the quadriceps muscle will help reduce the risk of further knee injury, and controlled swelling will also speed the return of muscle function. Conclusion: The present case conclude that the physiotherapy rehabilitation program on post PCL reconstruction can have a good effect on improvement of knee ROM and muscle strength.